2008
DOI: 10.1086/526463
|View full text |Cite
|
Sign up to set email alerts
|

A Search for Phylogenetically Informative Pollen Characters in the Subtribe Salviinae (Mentheae: Lamiaceae)

Abstract: The pollen morphology and ultrastructure of the subtribe Salviinae were investigated with light, scanning electron, and transmission electron microscopy. In addition, cladistic analyses of the obtained morphological data, supplemented with rbcL data from GenBank, were conducted in order to assess the phylogenetic signal of palynological characters. Salviinae pollen is small to large, oblate to prolate in shape, with a circular to slightly elliptic amb, and mostly hexacolpate. Perovskia abrotanoides appears to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 30 publications
4
54
0
Order By: Relevance
“…An operculum with granule was seen in all the taxa (Figures 1-3). Similarly, some authors (Perveen and Qaiser, 2003;Moon et al, 2008c;Hassan et al, 2009) found colpi with granulate membranes and pointed, acute, and obtuse ends. The exine is semitectate (Walker, 1974;Hamzaoğlu et al, 2005;Jafari and Nikian, 2008) and muri are simply columellate (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…An operculum with granule was seen in all the taxa (Figures 1-3). Similarly, some authors (Perveen and Qaiser, 2003;Moon et al, 2008c;Hassan et al, 2009) found colpi with granulate membranes and pointed, acute, and obtuse ends. The exine is semitectate (Walker, 1974;Hamzaoğlu et al, 2005;Jafari and Nikian, 2008) and muri are simply columellate (Figures 4 and 5).…”
Section: Discussionmentioning
confidence: 76%
“…These results agree with those of Özler et al (2011) (Figures 1 and 2). Similarly, Moon et al (2008c) The pollen grains of the Salvia taxa examined are small to large (P = 25.0-61.4 µm, E = 30.7-67.2 µm). The smallest pollen occurs in Salvia aethiopis, belonging to sect.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations